IMPRESSION INTELLECTUAL CAPITAL AND RISK PROFILE ON PROFITABILITY - Neny Tri Indrianasari; Khoirul Ifa; Muhamad Ali (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
The importance of intellectual capital aspects for companies makes this topic interesting to be researched today, especially related to the contribution of IC in encouraging company performance. Profitability is an appropriate benchmark in measuring the performance of a bank. One measure of profitability used is Return on Equity (ROE). ROE is used to measure the effectiveness of a company in generating profits by utilizing the equity it has. This study aims to determine the Impression of Intellectual Capital and Risk Profile on Profitability of BPR Syariah in East Java Province. This type of research used in this research is descriptive research with a quantitative approach. The population used in this study were all Sharia Rural Banks (BPRS) of East Java Province which were recorded in the Financial Services Authority (OJK) for the selected period of 2015-2018 with a total population of 26 banks. The sample in this study was selected by purposive sampling. This study concludes that the NPF ratio has no effect on ROE. Except for Intellectual Capital and FDR it has a significant influence on ROE.